PERFORMANCE EFFECTIVENESS- AN ACCOMPLISHING TOOL FOR THE EMPLOYEES OF BPO COMPANIES - Dr.B.Aiswarya, M.Sudha Paulin (International Journal of Advanced Science and Technology, 2020)
Traditional insight in business environment implicates that an employee’s past performance helps in the better prediction of his/her future performance. Business organizations both in the private and public sector across the world depend on their workforce for optimum performance effectiveness which will in turn yields to organisational efficiency. In this case, the need for considering employee job performance becomes a matter of requisite to every competitive business organization. To understand the better employees’ constructiveness on jobs, it is essential to comprehend about the relationships between job performance, people, and the related situation factors. Performance is the deciding phenomenon for organizations as employees’ performance always leads to business success. The success of any working organization relies on the involved contribution and job performance of their employees. They acts as the backbone who is responsible in achieving the organizational vision and the goals. Employee’s approachable attributes and the committed feelings towards the task they undertake lead to organisational effectiveness. The main objective of this study is to analyse and understand the level of performance effectiveness of the people working in BPO companies in Chennai city. For this purpose, a sample of 236 employees were taken from different BPO companies in Chennai city. The relationship between the different factors that’s contribute to the performance effectiveness were studied through the responses of the employees from the circulated questionnaires and the results were analysed. Due to the cut-throat competition among the BPO companies how they are maintain their level of performance system to retain and motivate efficient employees in their organization. Therefore the present study is carried out to observe and analyse the effectiveness of performance system in BPO companies in Chennai city.